The history of techniques (Gordon and Breach Science Publishers, 1986)
The history of various climbing and mountaineering techniques stretches as far back in the past as the first activity of a person in the mountains. While the first trip to the mountains were motivated by non-sporting interests entirely, nonetheless the techniques of progress which made the first mountain expeditions possible were developed at that time. The beginnings of the development of specialised climbing techniques in the modern sense of the word can be dated at least to Europe in the 16th century, when the hunting of chamois or the collection of minerals for jewellery purposes began to spread, particularly in the Alps. The majority of hunters or mineral collectors were recruited from the residents of mountain villages and gradually became sought-after mountain guides. In those days people headed into the mountains out of a desire for learning reflected in the dissemination of knowledge of the ductility of the landscape.